A direct methanol fuel cell system to power a humanoid robot - Joh, Han-Ik; Ha, Tae Jung; Hwang, Sang Youp; Kim, Jong-Ho; Chae, Seung-Hoon; Cho, Jae Hyung; Prabhuram, Joghee; Kim, Soo-Kil; Lim, Tae-Hoon; Cho, Baek-Kyu; Oh, Jun-Ho; Moon, Sang Heup; et al. (ELSEVIER SCIENCE BV, 2010)
In this study, a direct methanol fuel cell (DMFC) system, which is the first of its kind, has been developed to power a humanoid robot. The DMFC system consists of a stack, a balance of plant (BOP), a power management unit (PMU), and a back-up battery. The stack has 42 unit cells and is able to produce about 400 W at 19.3 V. The robot is 125 cm tall, weighs 56 kg, and consumes 210 W during normal operation. The robot is integrated with the DMFC system that powers the robot in a stable manner for more than 2 h. The power consumption by the robot during various motions is studied, and load sharing between the fuel cell and the back-up battery is also observed. The loss of methanol feed due to crossover and evaporation amounts to 32.0% and the efficiency of the DMFC system in terms of net electric power is 22.0%. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: SENSOR-LESS CONTROL; PORTABLE APPLICATIONS; STACK; PERFORMANCE; OPERATION